Analysis of the Influence of IPFC-POD and PSS controllers coordinated tuning by an Adaptive Genetic Algorithm with Hyper-mutation - Cordero Bautista, Luis Gustavo [UNESP]; Araujo, Percival Bueno de [UNESP]; IEEE (Ieee, 2018)
Small-magnitude disturbances happen to produce electro-mechanical oscillations which should be damped as quickly as possible to ensure reliability and stability of electrical power system (EPS). Flexible AC transmission systems (FACTS) are a modern technology to increase controllability in power systems. This paper presents an analysis of Interline Power Flow Controller (IPFC), which is a FACTS device based on Voltage Source Controller (VSC). The electric power system and IPFC FACTS device get represented by a current sensitivity model (CSM). This work focuses on small-signal stability studies using an Adaptive Genetic Algorithm with Hyper-mutation (AGAH) for tuning Power System Stabilizers (PSS) and IPFC with Power Oscillation Damping (POD) controllers in a coordinated way. AGAH aims to find optimal controller parameters to enhance poor damping of local and inter-area low frequency oscillations. Two areas 14 bus symmetrical system is considered in order to assess proposed algorithm. Simulations are carried out in MatLab platform in order to compare genetic algorithm (GA) with proposed algorithm performance. Results show AGAH yields more accurate damping value and gets convergence faster than the simple GA.
Keywords: Small-signal Stability; Power System Stabilizer; Interline Power Flow Controller; Power Oscillation Damping; Adaptive Genetic Algorithm; Hyper-mutation